Yerba Mate, Intangible Heritage and Soft Power in the Time of Juan Manuel de Rosas (1829-1852); [Yerba Mate, Patrimonio Inmaterial y Poder Blando en Tiempos de Juan Manuel de Rosas (1829-1852)1] - Lacoste, P (Universidade de Sao Paulo, Faculdade de Filosofia, Letras e Ciencias Humanas, 2024)
We examine the valuation of yerba mate as a regional agro-food heritage in the process of the construction of the Americanist ideology during the administration of Juan Manuel de Rosas at the head of the Argentine Confederation. The yerba mate culture was deeply rooted in Southern Cone society in the seventeenth and eighteenth centuries, but, after independence, British commercial strategy sought to replace it with tea, an imperial product that served their interests. This project was successful in several territories, for example in Chile, where the elite followed the fashion imposed by the British. But in the Río de la Plata, Rosas was determined to promote and strengthen the mate culture as a strategic means of asserting an Americanist identity and resisting European neo-colonial pretensions. With this attitude, Rosas was a pioneer in the valuation of the regional agro-food heritage. © 2024 Universidade de Sao Paulo, Faculdade de Filosofia, Letras e Ciencias Humanas. All rights reserved.